Bone allograft impregnated with tobramycin and vancomycin delivers antibiotics in high concentrations for prophylaxis against bacteria commonly associated with prosthetic joint infections - Björn Berglund; Daphne Wezenberg; Maud Nilsson; Bo Söderquist; Lennart E. Nilsson; Jörg Schilcher (Microbiology Spectrum)
ABSTRACT Local delivery of antibiotics as prophylaxis for prosthetic joint infections (PJIs) is frequently used during total hip replacement surgery. Morselized bone allograft impregnated with vancomycin and tobramycin (TobraVanc) could provide effective prophylaxis against bacteria commonly associated with PJIs. In this study, the concentrations of antibiotics released by bone allograft impregnated with TobraVanc were determined by using an in vitro bioassay system entailing measuring inhibition zone diameters caused by antibiotic-impregnated bone chips cast in agar against standard curves. The concentrations were determined in samples of TobraVanc-impregnated bone graft taken before and after the application of the bone graft in the patients undergoing acetabular revision surgery. Antibiotic-impregnated bone grafts, sampled prior to application in the patient, delivered antibiotics in the concentration ranges of 730–9,800 mg/L for tobramycin and 1,300–11,000 mg/L for vancomycin. Samples taken after application in the patient released lower concentrations of tobramycin (490–1,900 mg/L; P < 0.01) and vancomycin (3,000–5,100 mg/L; P < 0.05); however, these concentrations remained well above the tobramycin minimum inhibitory concentrations (MICs) for investigated, highly tobramycin-resistant Staphylococcus epidermidis strains (MICs > 256 mg/L). At the tested concentrations, bone graft material mixed with TobraVanc delivered antibiotics in potent concentrations above the MICs for bacteria causing PJIs. Clinical trials are needed to evaluate the efficacy and risk of TobraVanc-impregnated bone graft as a prophylactic agent for patients undergoing hip replacement surgery.IMPORTANCEAntibiotic prophylaxis is the cornerstone of successful joint replacement surgery, reducing the risk for the dreaded complication of prosthetic joint infection (PJI) to roughly 0.5%–2% in standard total hip replacement (THR). In addition to systemic antibiotics, antibiotics added locally have the potential to reduce the PJI risk even further, because of the high concentrations that can be achieved in the joint with limited risk for systemic toxicity. The results in the current study show that bone chips impregnated with a combination of tobramycin and vancomycin (TobraVanc) release antibiotics in concentrations that are potent against common bacteria causing PJIs. Especially in high-risk patients, our results support the prophylactic use of TobraVanc in hip replacement surgery requiring the use of a bone graft. A clinical study testing the efficacy of TobraVanc-impregnated bone graft in reducing the incidence of PJI in hip replacement surgery is currently ongoing (EudraCT: 2021-001708-14).